GIS based assessment on landslide hazard zonation - Mohamed M Gahgah, Juhari Mat Akhir, Abdul Ghani M Rafek, Ibrahim, . (2009)
The aim of this study is to investigate the factors that cause landslides in the area along the new road between Cameron Highlands and Gua Musang. Landslide factors such as lineaments have been extracted from remote sensing data (Landsat TM image) using ERDAS software.